Bioactivity-Guided Isolation of Secondary Metabolites with Antioxidant and Antimicrobial Activities from Camellia fascicularis - Ruonan Li; Jiandong Tang; Jingjing Li; Boxiao Wu; Junrong Tang; Huan Kan; Ping Zhao; Yingjun Zhang; Weihua Wang; Yun Liu (Foods, 2024)
Camellia fascicularis has important ornamental, medicinal, and food values, which also have tremendous potential for exploiting bioactivities. We performed the bioactivity-guided (antioxidant and antimicrobial) screening of eight fractions obtained from the ethyl acetate phase of C. fascicularis. The antioxidant activity was measured by DPPH, ABTS, and FRAP, and the antibacterial activity was measured by the minimum inhibitory concentration (MIC) of Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus. The results of bioactivity-guided isolation indicated that the major antioxidant compounds in the ethanolic extracts of C. fascicularis may be present in fractions (Fr.) (A–G, obtained after silica gel column chromatography). Fr. (D–I, obtained after silica gel column chromatography) is a fraction of C. fascicularis with antimicrobial activity. The structures of compounds were determined by spectral analysis and nuclear magnetic resonance (NMR) combined with the available literature on secondary metabolites of C. fascicularis leaves. In this study, 17 compounds were identified, including four phenolics (1, 3–4, and 14), a phenylpropane (2), five terpenoids (5–7, 12, and 15), four flavonoids and flavonoid glycosides (8–10 and 16), and two lignins (13 and 17). Compounds 4–7, 13–15, and 17 were isolated from the genus Camellia for first time. The remaining compounds were also isolated from C. fascicularis for first time. The evaluation of antioxidant and antimicrobial activities revealed that compounds 1, 3, 9, 11, and 17 exhibited higher antioxidant activity than the positive control drug (ascorbic acid), and compounds 4, 8, 10, and 13 showed similar activity to ascorbic acid. The other compounds had weaker or no significant antioxidant activities. The MIC of antibacterial activity for compounds 4, 7, and 11–13 against P. aeruginosa was comparable to that of the positive control drug tetracycline at 125 µg/mL, and other secondary metabolites inhibited E. coli and S. aureus at 250–500 µg/mL. This is also the first report of antioxidant and antimicrobial activities of compounds 5–7, 13–15, and 17. The results of the study enriched the variety of secondary metabolites of C. fascicularis and laid the foundation for further research on the pharmacological efficacy and biological activity of this plant.